What is the Doctrine of the Trinity For? Practicality and Projection in Robert Jenson's Theology. (20th March 2017) - East, Brad
Abstract: This articles engages the theology of Robert Jenson with three questions in mind: What is the doctrine of the Trinity for? Is it a practical doctrine? If so, how, and with what implications? It seeks, on the one hand, to identify whether Jenson's trinitarian theology ought to count as a "social" doctrine of the Trinity, and to what extent he puts it to work for human socio‐practical purposes. On the other hand, in light of Jenson's career‐long worries about Feuerbach and projection onto a God behind or above the triune God revealed in the economy, the article interrogates his thought with a view to recent critiques of social trinitarianism. The irony is that, in constructing his account of the Trinity as both wholly determined in and by the economy and maximally relevant for practical human needs and interests, precisely in order to avoid the errors of Feuerbachian "religion, " Jenson ends up engaging in a full‐scale project of projection. Observation of the human is retrojected into the immanent life of the Trinity as the prior condition of the possibility for the human; upon this "discovery, " this or that feature of God's being is proposed as a resolution to a human problem, bearing ostensibly profound socio‐practical import. The article is intended, first, as a contribution to the work, only now beginning, of critically receiving Jenson's theology; and, second, as an extension of general critiques of practical uses of trinitarian doctrine, such as Karen Kilby's or Kathryn Tanner's, by way of close engagement with a specific theologian.